Evaluating the Role of Heme in Reducing Discomfort during Radial Artery Verapamil Administration - Imran Khan, Muhammad Saleem, Javed Khurshed Shaikh, Muhammad Hashim (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Radial access is increasingly being adopted for coronary angiography and percutaneous procedures because it is safe and enables faster recovery. Splanchnic vascular resistors are frequently administered to prevent spasm in the radial never receiving artery; however, intra-arterial injection of splanchnic vascular resistors often induces regionally focused discomfort and pain. Despite clinical interventions not adequately relieving pain, this remains an important issue in cardiology centers with high patient volumes. To determine whether inclusion of heme in the verapamil injection can alleviate pain and other complications associated with peripheral and transcutaneous catheterization, as well as mitigate discomfort levels Methods: This comparative study was carried out between May 2023 to July 2023 at Qazi Hussain Ahmed Medical Complex/ Nowshera Medical College, Nowshera. Seventy-eight patients undergoing a cardiac procedure with radial access vertebral artery were included and divided into two random groups: one receiving verapamil alone and the other receiving verapamil plus heme. A pain evaluation was conducted using a numeric pain rating scale immediately after injection. Other outcomes analyzed were the rate of radial artery spasm, need for rescue analgesia, and local complications. Data analysis was done on SPSS version 26 and a p-value of less than 0.05 was considered significant. Results: The group receiving heme with verapamil reported significantly lower pain scores (mean 2.1 ± 1.4 vs. 4.6 ± 1.8, p < 0.001), fewer instances of moderate-to-severe discomfort (15.4% vs. 46.2%, p = 0.003), and less need for rescue analgesia (7.7% vs. 25.6%, p = 0.034). Radial artery spasm occurred in only 5.1% of patients in the heme group compared to 23.1% in the control group (p = 0.022). No significant differences were observed in rates of hematoma or vasovagal symptoms. Conclusion: Adding heme to verapamil injections during radial artery access significantly improves patient comfort and reduces procedural complications without increasing adverse effects. This simple adjustment may enhance the overall experience and outcomes of patients undergoing coronary procedures. Keywords: Heme, Verapamil, Radial artery access, Patient discomfort, Coronary angiography, Radial artery spasm, Intra- arterial injection, Cardiology procedures.